Changes in accrual properties and operating environment: Implications for cash flow predictability - Nallareddy, Suresh; Sethuraman, Mani; Venkatachalam, Mohan (Journal of Accounting and Economics, 2020)
This paper reconciles conflicting evidence in prior literature on the relative ability of earnings and cash flows in predicting future cash flows. Further, we investigate the implications of temporal shifts in accrual properties and operating environment for cash flow predictability. Three key insights emerge. First, cash flows consistently outperform earnings in predicting future cash flows. Second, accruals and its components, including those capturing non-articulating events, have incremental (albeit small) predictive ability over cash flows. Third, earnings’ ability to predict future cash flows has increased over the period 1989–2015, due to changes in operating environment rather than accrual properties.